PENGARUH MOTIVASI, DAN KEPEMIMPINAN TERHADAP KINERJA DOSEN DIMEDIASI KOMPETENSI (Studi Kasus Terhadap Dosen Pada Akademi Kepolisian) (Jurnal Mahasiswa Pasca Sarjana, 2014)
This study aimed to examine the effect of motivation and leadership on the performance of faculty competence mediated (A Case Study of the lecturer at the Police Academy). This type of research is used in the preparation of this thesis is explanatory research (explanatory research), using multiple linear regression analysis model. In this study population used was the whole power of education (lecturer) at the Police Academy some 84 people. Questionnaires were distributed and the data were analyzed by 84. Hypothesis test results showed that the overall hypothesis tested in this study received:Work motivation positive and significant effect on the competence of a lecturer at the Police Academy in Semarang, Leadership positive and significant effect on the competence of a lecturer at the Police Academy in Semarang, Work motivation positive and significant effect on the performance of a lecturer at the Police Academy in Semarang, Leadership positive and significant effect on the performance of a lecturer at the Police Academy in Semarang, Competence positive and significant effect on the performance of a lecturer at the Police Academy in Semarang and While not mediate competence variables for all variables. Keywords: Motivation, Leadership, Competence, Performance.